Presence of Cervical Vertebral Anomalies with Concomitant Non-Communicating Hydrocephalus and Multicystic Kidney in a Female Fetus: Where VACTERL-H Meets MURCS. (15th October 2021) - Dracopoulos, Christoph; Gembicki, Michael; Scharf, Jann Lennard; Welp, Amrei; Berg, Nadine; Weichert, Jan
ABSTRACT: Background: Congenital multisystemic lesions with co-occurrence of non-random malformations, such as VACTERL-H or MURCS association, often pose serious threads to the newborn and still constitute an antenatal diagnostic dilemma. Case report: A malformed fetus with VACTERL-H association at 20 gestational weeks had a skin-covered neural tube defect (NTD) of the lower cervical spine, concomitant hydrocephalus, as well as unilateral multicystic dysplastic kidney and the suspicion of mullerian duct anomaly as potentially assigned to MURCS association. Discussion/Conclusion: We were able to demonstrate how well-defined, standardized volumetric reconstruction of diagnostic views displaying fetal pathology in utero might aid early and precise diagnosis of multi-organ malformations. Application of modern diagnostic imaging tools is helpful in delineation of the most likely diagnoses (VACTERL-H vs. MURCS) as further specified during detailed pathologic work-up and might consequently facilitate individually tailored interdisciplinary counseling, as in the case presented here.